BLENDED LEARNING IN HIGHER EDUCATION: MULTIPLE CASE STUDY - Savione Machado, Nathália; Mattar, Joao (Interacções, 2020)
This research explores the possible combinations between face-to-face, blended and distance learning. It has the general objective of analyzing the participation and interaction of the students in two pedagogical models of the face-to-face higher education. Its field of study is two higher education institutions in Brazil, one public and the other private, with two locational undergraduate courses, which use up to 20% of the total hours of the course in distance education. It is characterized as a multiple case study. The exploratory type qualitative approach is used, having as corpus the institutional documents, the reports of participant (unstructured) observation in six disciplines and the statements of 70 students, collected through the application of the following research instruments: a semi-structured questionnaire and interviews. For the analysis of the data, the methodology of content analysis proposed by Bardin (2011) was used. The results, based on the students’ speech, reinforce the desire for a truly hybrid education that connects the modalities, which allows the student to have more autonomy and protagonism and values the teacher as mediator.